Performance comparison of two malaria rapid diagnostic test with real time polymerase chain reaction and gold standard of microscopy detection method - Puspa Wardhani; Trieva Verawaty Butarbutar; Christophorus Oetama Adiatmaja; Amarensi Milka Betaubun; Nur Hamidah; Aryati (MDPI AG, 2020)
Background: The diagnostic test for malaria is mostly based on Rapid Diagnostic Test (RDT) and detection by microscopy. Polymerase Chain Reaction (PCR) is also a sensitive detection method that can be considered as a diagnostic tool. The outcome of malaria microscopy detection depends on the examiner's ability and experience. Some RDT has been distributed in Indonesia, which needs to be evaluated for their results. Objective: This study aimed to compare the performance of RightSign RDT and ScreenPlus RDT for detection of Plasmodium in human blood. We used specific real-time polymerase chain reaction abTESTMMalaria qPCRII) and gold standard of microscopy detection method to measure diagnostic efficiency. Methods: Blood specimens were evaluated using RightSign RDT, ScreenPlus RDT, Microscopy detection, and RT-PCR as the protocol described. The differences on specificity (Sp), sensitivity (Sn), positive predictive value (PPV), and negative predictive value (NPV) were analyzed using McNemar and Kruskal Wallis analysis. Results: A total of 105 subjects were recruited. Based on microscopy test, RightSign RDT had sensitivity, Specificity, PPV, NPV, 100%, 98%, 98.2%, 100%, respectively. ScreenPlus showed 100% sensitivity, 98% specificity, 98.2% PPV, 100% NPV. The sensitivity of both RDTs became lower (75%) and the specificity higher (100 %) when using real-time PCR. Both RDTs showed a 100% agreement. RT-PCR detected higher mix infection when compared to microscopy and RDTs. Conclusion: RightSign and ScreenPlus RDT have excellent performance when using microscopy detection as a gold standard. Real-time PCR method can be considered as a confirmation tool for malaria diagnosis.